Redox regulation of sarcoplasmic reticulum calcium cycling in the heart - Donoso, Paulina (2013)
The coordinated release and reuptake of calcium into the sarcoplasmic reticulum (SR) is critical to maintain an adequate heart function. Reactive oxygen species (ROS) and reactive nitrogen species (RNS), generated in the heart under normal basal condition, modulate the function of different proteins via the reversible oxidation of critical cysteine residues. Excess ROS/RNS generation has been shown to impair heart function, but extensive evidence indicates that the controlled production of these molecules increases cardiac contractility by targeting SR calcium proteins. Ryanodine receptors (RyR2) are endogenously S-nitrosylated and S-glutathionylated and both redox modifications increase the activity of these channels in vitro. Moreover, exercise or rapid pacing increases the RyR2 S-glutathionylation, a modification that depends on the activation of NADPH oxidase (NOX2). In isolated cardiomyocytes, this enzyme is rapidly activated by stretch, generating an immediate burst of ROS which increases calcium release by RyR2. Nitroxyl, a particular ROS/RNS, increases cardiac inotropy in vivo, by targeting critical thiols in RyR2, the SR Ca2+-ATPase and phospholamban, allowing the simultaneous increase in calcium release and reuptake, required to produce a sustained increase in the calcium transient. In this minireview we present some of the recent work on the redox regulation of SR calcium cycling proteins.